«IT IS REPARABLE HISTORICAL JUSTICE …»: FAR EAST CAMPAIGN OF 1945 IN CONSCIOUSNESS OF THE SOVIET MILITARY PERSONNEL - E. S. Senyavskaya (MGIMO University Press, 2013)
In this article on the basis of documentary evidence and memories of the participants of the events shows, what was the sentiments in the summer of 1945, after the victory over Germany, when the Soviet troops departed from Europe to the far East, to participate in the war with Japan, and how the Soviet command solved a difficult problem - to mobilize for perform the new military tasks people who were weary up to the limit from years of war, dreamed of a speedy return to their families and relatives on. Also review the features of the preparation for a new war veterans of European fights and “dalnevostochny stays”, with the consideration of rich combat experience of the first category of servicemen and better knowledge of the natural-climatic conditions of the forthcoming theatre of war the second category. In article analyzes massive army representation of the Japanese as a military rival and their correspondence to reality. Underestimation of the enemy in the first days of the war led to a “criminal carelessness” and losses, so the commanders had to strengthen explanatory work with staff about insidiousness of the enemy and vigilance increase. The bitterness of the fighting shows in widespread phenomenon of “kamikaze bombers. Special attention is paid to violations of the Japanese party norms of international law, the laws and customs of war. In conclusion it is shown that the military campaign of the Soviet army in the far East not only hasten the end of the Second world war and provided a new balance of strategic forces in the postwar world, but also contributed to the eventual eradication of complex of a defeated country, inherited from tsarist Russia.